Ethical consideration on use of seclusion in mental health services - Chaodun Zheng; Sijue Li; Yingmei Chen; Junrong Ye; Aixiang Xiao; Zhichun Xia; Yao Liao; Yu Xu; Yunlei Zhang; Lin Yu; Chen Wang; Jiankui Lin (Elsevier, 2020)
Seclusion was widely used in mental health service, which had caused various negative effects on patients and nurses. In China, the clinical use of seclusion was gradually increasing, which had led to ethical dilemma and had gained public concern. This article aimed to synthesize the ethical issue according to the principle of autonomy, justice, beneficence, and non-maleficence. Given that nursing workforce was limited and work burden among psychiatric nurses was heavy, seclusion was one of coercive interventions managing aggressive behavior. In relation to cope with ethical dilemma, it was proposed to improve therapeutic environment, and to apply de-escalation technique. Additionally, reducing clinical use and adverse effects of seclusion was also important, this goal would be achieved by building appropriate patient-nurse relationship, increasing staff engagement, and promoting guideline of seclusion. Keywords: Psychiatric hospitals, Nursing ethics, Patient isolatio